Supporting the digital transformation of SMEs — trained digital evangelists facilitating the positioning phase - Kääriäinen, Jukka; Saari, Leila; Tihinen, Maarit; Perätalo, Sari; Koivumäki, Timo (International Journal of Information Systems and Project Management, 2023)
As digital transformation (DT) sweeps over society, the exploitation of digital solutions is obvious, especially for large enterprises. Unfortunately, small- and medium-sized enterprises (SMEs) struggle with DT because of limited resources, understanding, and implementation skills. Thus, SME companies need both methods and tools to proceed with DT as well as support to exploit them. This article presents a study in which adult learners with professional experience are trained to use a digitalization development method and tools to analyze target organizations’ digitalization state and identify improvement ideas. Thirty trained digital evangelists used the tools and methods while conducting digitalization status analyses in eleven organizations. The study results show that the method and tools work in the context presented in this research. The study’s findings are beneficial for the educational professionals interested in educating students towards helping SME organizations along their digitalization pathway.